EFFECT OF MAGNESIUM SULPHATE NEBULIZATION ON THE INCIDENCE OF POSTOPERATIVE SORE THROAT IN PATIENTS REQUIRING ENDOTRACHEAL INTUBATION FOR GENERAL ANESTHESIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Postoperative sore throat (POST) is a common and distressing complication following endotracheal intubation under general anesthesia. Airway mucosal irritation and inflammation play a significant role in its pathogenesis. Magnesium sulphate, owing to its anti-inflammatory and antinociceptive properties, may reduce the incidence and severity of POST when administered as nebulization prior to induction of anesthesia. Aim: To evaluate the effect of preoperative magnesium sulphate nebulization on the incidence and severity of postoperative sore throat in patients undergoing surgery under general anesthesia with endotracheal intubation. Materials and Methods: This prospective randomized controlled study was conducted at Dhanalakshmi Srinivasan Institute of Medical Sciences and Hospital over a period of six months from July 2025 to December 2025. A total of 100 patients aged 20–65 years, belonging to ASA physical status I and II, scheduled for elective surgery under general anesthesia with endotracheal intubation were enrolled. Patients were randomly allocated into two groups of 50 each. The control group received nebulization with normal saline, while the study group received nebulization with magnesium sulphate prior to induction of anesthesia. The incidence and severity of postoperative sore throat were assessed at 0, 2, 4, 12, and 24 hours post-extubation. Results: The incidence and severity of postoperative sore throat were significantly lower in the magnesium sulphate group compared to the control group, particularly at 4, 12, and 24 hours postoperatively. No significant adverse effects related to magnesium sulphate nebulization were observed. Conclusion: Preoperative nebulization with magnesium sulphate is a safe, simple, and effective method for reducing the incidence and severity of postoperative sore throat in patients undergoing general anesthesia with endotracheal intubation.